Prognostic Nutritional Index (PNI) as a Prognostic Factor in Stage IV Lung Adenocarcinoma - Subroto, Subroto; Budiono, Eko; Sumardi, Sumardi (Faculty of Medicine Universitas Gadjah Mada, 2021)
Background. Based on nutritional and immunological indicators, the Prognostic Nutritional Index (PNI) is one of the prognostic indicators besides the Platelet-to-Lymphocyte Ratio (PLR) and Glasgow Prognostic Score (GPS). PNI can serve as a biomarker to help guide clinical practice and promote clinical outcomes for lung cancer patients. PNI was superior to Neutrophil- to- Lymphocyte Ratio (NLR) in the prediction of progression-free survival (PFS) and overall survival (OS). Objectives. To analyze the association between a low PNI score (PNI <40) and increased risk of mortality among stage IV pulmonary adenocarcinoma patients.Methods. A cohort-retrospective study was performed by extracting PNI data from medical records and the mortality of patients with stage IV pulmonary adenocarcinoma. A total of 265 patients met the inclusion and exclusion criteria, based on the medical records of patients with stage IV pulmonary adenocarcinoma who were hospitalized at Dr. Sardjito hospital Yogyakarta between January 1st, 2016 and July 1st, 2019. PNI score were calculated as follows: 10 x serum albumin (g/dl) + 0.005 x lymphocyte count (per mm3). Mortality was considered six months since the diagnosis. Chi-square tests were used to analyze the proportions of mortality and confounders. Multiple logistic regression tests were used to analyze the association between PNI and mortality.Results. Subjects with PNI score <40 were at risk of mortality three times higher than subjects with PNI score ≥40 (adjustedOR 3.356, 95% CI 1.165 - 9.670, p = 0.025).Conclusion. PNI score significantly affected the mortality in patients with stage IV pulmonary adenocarcinoma.